Desain Kemasan Racikan Jamu Herbal Baristo Jumo Sebagai Media Promosi - Ananda Ayu Zanira; Elfa Olivia Verdiana; Faldi Hendrawan (Jurnal Desain Komunikasi Visual Asia, 2023)
The Javanese people in particular have consumed herbal medicine (jamu) as a prevention, inhibitor, and antidote ti disease in the body by extracting nutritious extracts from various herbs and spices into drinkable liquid. Baristo Jumo is one of the herbal drink providers. It’s just that Baristo Jumo’s promotion is still experiencing difficulties because the packaging has not reached its most potential use. The solution offered in this research is to design packaging for Baristo Jumo mixed herbal jamu as promotional media. Packaging is a medium that directly deals with consumers, so it must be able to give a good impression. The test results using questionnaire filling method in his study showed 89,6% of “YES”, which means that the packaging design for Baristo Jumo was successful and able to attract consumers’ attention.